Comparison of Hypertonic Saline vs Salbutamol in Normal Saline Nebulization in Children with Bronchiolitis - Anjum Ali, Hafiz Muhammad Muaaz Naeem, Arshad Rafique, Sijjad Hussain, Makhdoom Rasheed, Muhammad Uzair, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Main stay of treatment of acute Bronchiolitis is general supportive care, such as oxygenation, aspiration of respiratory tract secretions, and hydration therapy. Recent research indicates that breathed hypertonic saline is a potential treatment. Objective: To compare the mean length of hospital stay and clinical bronchiolitis score of salbutamol nebulized in normal saline versus hypertonic saline in children with acute bronchiolitis. Material and methods Study Design: Randomized controlled design Setting: Department of pediatrics, Fatima Memorial Hospital, Lahore. Duration of Study: 6 months after approval of the study i.e. from 12th April 2017 to 12th October 2017. Data Collection Procedure: Relevant parameters were identified, and the CBSS was computed. Using random tables, cases were divided among two groups and given salbutamol or hypertonic saline nebs. The length of stay was determined. The Clinical Bronchiolitis Severity Score (CBSS) was recorded based on various variables. Version 17 of the statistical package for social sciences was used for statistical analysis. Result: Patients in the salbutamol group had a mean age of 13.56.66 months, while those in the hypertonic saline group had a mean age of 12.46.58 months. In the group receiving salbutamol, there were 29 males and 31 females. There were 32 men and 28 women in the hypertonic saline group. After 24 hours, the mean CBSS in the salbutamol group was 6.132.47, whereas in the hypertonic saline group, it was 4.881.75. After 24 hours of treatment, the difference in CBSS was significant between the two groups (P0.05). The mean duration of hospitalization was 3.920.81 days with salbutamol and 3.050.77 days with the hypertonic group. In both groups, there was a marked difference in duration of hospital stay (P0.05). Conclusion: Thus, hypertonic saline was more effective than salbutamol in reducing the CBSS score and duration of hospital stay. Keywords: Hospital Stay, Clinical Bronchiolitis Score, Nebulized Salbutamol, Normal Saline, Hypertonic Saline, Children, Acute Bronchiolitis.